Empirical Comparison of Diffusion Kurtosis Imaging and Diffusion Basis Spectrum Imaging Using the Same Acquisition in Healthy Young Adults - Wang, Sijia; Peterson, Daniel J.; Wang, Yong; Wang, Qing; Grabowski, Thomas J.; Li, Wenbin; Madhyastha, Tara M. (Frontiers in Neurology, 2017)
As Diffusion Tensor Imaging (DTI) gains widespread use, many researchers have been motivated to go beyond the tensor model and fit more complex diffusion models, to gain a more complete description of white matter microstructure and associated pathology. Two such models are Diffusion Kurtosis Imaging (DKI) and Diffusion Basis Spectrum Imaging (DBSI). It is not clear which DKI parameters are most closely related to DBSI parameters, so in the interest of enabling comparisons between DKI and DBSI studies, we conducted an empirical survey of the inter-relation of these models in 12 healthy volunteers using the same diffusion acquisition. We found that Mean Kurtosis (MK) is positively associated with the DBSI Fiber Ratio, and negatively associated with the Hindered Ratio. This was primarily driven by the radial component of kurtosis. The axial component of kurtosis was strongly and specifically correlated with the Restricted Ratio. The joint spatial distributions of DBSI and DKI parameters are tissue-dependent and stable across healthy individuals. Our contribution is a better understanding of the biological interpretability of the parameters generated by the two models in healthy individuals.